Przewalski’s Horses (Equus ferus przewalskii) Responses to Unmanned Aerial Vehicles Flights under Semireserve Conditions: Conservation Implication - Lu, Vanessa; Xu, Feng; Turghan, Mardan Aghabey (International Journal of Zoology, 2021)
Recent technological innovations have led to an upsurge in the availability of unmanned aerial vehicles (also known as drones and hereafter referred to as UAVs)—aircraft remotely operated from the ground—which are increasingly popular tools for ecological research, and the question of this study concerns the extent to which wildlife responses might allow aerial wildlife monitoring (AWM) by UAVs. Our experiment tests the hypothesis that the wildlife-UAVs interaction depends strongly on flight altitude that there may be a lowest altitude range for which the ungulates are not exceedingly disturbed, dictating a practically achievable level of discernibility in flight observation, for this question might influence the future viability of the UAVs in the study and protection of the other wildlife in China’s semiarid ecosystem. We examined the behavioral responses of a group of enclosed Przewalski’s horses (Equus ferus przewalskii) to the presence of different in-flight UAVs models by conducting flights at altitudes ranging from 1 to 52 meters and recorded the heights at which each horse reacted to (noticed and fled) the UAVs. All horses exhibited a stress response to UAVs flights as evidenced by running away. The results suggest strong correlations between flight altitude and response across the different subjects that adults generally noticed the UAVs at the larger heights (20.58 ± 10.46 m) than the immature (4.67 ± 0.87 m). Meanwhile, reaction heights of females (15.85 ± 6.01 m) are smaller than that of males (26.85 ± 18.52 m). Supported by their biological roles in herds (e.g., males must give protection to his entire herd while females are purely responsible for their offspring), our results also show that age, closely followed by gender, are the two most significant elements that determine a horse’s level of alertness to the UAVs. This research will help future scientists to better gauge the appropriate height to use a drone for animal observation in order to minimize disturbance and best preserve their natural behavior.